The application of synchrotron methods in characterizing iron and cobalt Fischer-Tropsch synthesis catalysts - Jacobs, G.; Ma, W.; Gao, P.; Todic, B.; Bhatelia, Tejas; Bukur, D.; Davis, B. (Elsevier BV, 2013)
This article reviews the use of synchrotron radiation techniques to confront issues associated with cobalt and iron catalysts. The main areas that are examined include: (1) the application of TPR-XANES and TPR-EXAFS to gain insight into the hydrogen reduction of cobalt catalysts and the carburization of iron catalysts; (2) the impact of promoters on these reduction/carburization rates; (3) the local atomic structure of promoters and its influence on catalyst selectivity; (4) exploring the deactivation of cobalt catalysts; (5) the influence of crystallite size in stabilizing cobalts catalyst against water effects; and (6) temperature effects in alkali promoted iron catalysts in retaining the iron carbide phase against reoxidation by water. Â© 2012 Elsevier B.V. All rights reserved.